Fuzzy Logic as A Method of Decision Making in Automatic Watering Plants - T. W. Matha; Agung Nugroho Jati; F. Azmi (JMECS (Journal of Measurements, Electronics, Communications, and Systems), 2016)
In this era of technology, the use of automatic control systems can provide some benefits in terms of efficiency, accuracy, and safety compared to that of manual workmanship. This study tries to create a control system that can perform automatic plant watering system to help us in watering plants. In this study, weather forecast and weather shield are integrated with microcontroller as to gather weather information in the area around the plants. The information is then compared for decision making in automatic watering. This study is derived from the growing popularity of the hobby to grow plants in community. However, the constraint of time and distance in growing plants becomes one of the problems for people who are busy with their activities so that they do not have time for watering plants.